Synthetic 5-amino-6-D-ribitylaminouracil paired with inflammatory stimuli facilitates MAIT cell expansion in vivo - Nelson, Adam G.; Wang, Huimeng; Dewar, Phoebe M.; Eddy, Eleanor M.; Li, Songyi; Lim, Xin Yi; Patton, Timothy; Zhou, Yuchen; Pediongco, Troi J.; Meehan, Lucy J.; Meehan, Bronwyn S.; Mak, Jeffrey Y. W.; et al. (Frontiers in Immunology, 2023)
Mucosal-associated invariant T (MAIT) cells are a population of innate-like T cells that mediate host immunity to microbial infection by recognizing metabolite antigens derived from microbial riboflavin synthesis that are presented by the MHC-I-related protein 1 (MR1). Namely, the potent MAIT cell antigens, 5-(2oxopropylideneamino)-6-D-ribitylaminouracil (5-OP-RU) and 5-(2-oxoethylideneamino)-6-Dribitylaminouracil (5-OE-RU) form via the condensation of the riboflavin precursor 5-amino-6-Dribitylaminouracil (5-A-RU) with the reactive carbonyl species (RCS) methylglyoxal (MG) and glyoxal (G), respectively. Although MAIT cells are abundant in humans, they are rare in mice, and increasing their abundance using expansion protocols with antigen and adjuvant has been shown to facilitate their study in mouse models of infection and disease. Here, we show that the administration of synthetic 5-A-RU in combination with one of three different inflammatory stimuli is sufficient to increase the frequency of MAIT cells in C57BL/6 mice. Our data provide alternative methods for expanding MAIT cells with high doses of commercially available 5-A-RU (± MG) in the presence of various danger signals without the use of synthetic 5-OP-RU.